My happiness and the happiness of others - Exploring interactive media pathways to sustainability communication - Dias, Carolina; Palma-Oliveira, José Mauel; Branquinho, Cristina; Mendes, Mónica (Proceedings of the Life Improvement in Quality by Ubiquitous Experiences Workshop (LIQUE); 2022: Proceedings of the 2nd Life Improvement in Quality by Ubiquitous Experiences Workshop, 2022)
The word Sustainability is increasingly used in a myriad of different contexts. Nevertheless, there is still little knowledge about how lay individuals understand the concept and its broadness, and how they can link it to their own well-being. The aim of this research is to explore the creation of public interactive artistic media experiences based on experts and lay individuals' mental models, in order to captivate, communicate and engage with sustainability as related to well-being